Hydrocephalus treated with VP shunt surgery: a clinical audit - Gautam, V K S; Singh, Ravinder; Khurana, Sarbjeet (International Journal of Health, 2014)
Hydrocephalus is a common disease of the brain. Ventriculoperitoneal shunt (VPS) surgery is one of the procedures for its treatment.  The clinical outcome following VPS should be evaluated periodically to reduce the complications associated with this procedure. Clinical audit helps to identify and develop effective methods for improvement in patient care.  This paper illuminates the experience of authors in clinical audit of forty three neurosurgical patient undergone VPS surgery. Keywords: Clinical Audit, Hydrocephalus, VP Shunt.